MENILAI KINERJA DAN KESEHATAN KEUANGAN BANK BTN MENGGUNAKAN PENDEKATAN CAMEL PERIODE 2022–2024 - Adhisa Nabila Syahla; Vella Azzahra; Irfan Gunawan; Hani Hatimatunnisani; Riffka Fauzany (LPPM Politeknik Pajajaran ICB, 2026)
This research examines the financial performance of PT Bank Tabungan Negara (Persero) Tbk for the 2022–2024 period by applying the CAMEL analysis framework. A descriptive quantitative method is employed, utilizing secondary data derived from BTN’s publicly available annual financial reports. The assessment focuses on several key financial indicators, namely Capital Adequacy Ratio (CAR), Asset Quality (KAP), Net Profit Margin (NPM), Return on Assets (ROA), Operating Expenses to Operating Income (BOPO), and Loan to Deposit Ratio (LDR). The findings reveal that, overall, Bank BTN maintained a sound financial condition throughout the observation period. The results indicate strong capital resilience, well-managed asset quality, relatively consistent profitability despite certain fluctuations, and sufficient liquidity levels. Accordingly, the CAMEL approach proves to be a reliable and effective method for evaluating the financial soundness and performance of Bank BTN.